(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
This article explores the development of a management strategy for real estate assets, with a particular focus on the housing sector. It highlights the significance of real estate as a management object and analyzes its social and commercial efficiency, types of housing stock, management directions, and existing challenges. The article emphasizes the importance of a strategic approach to managing urban residential property, which should encompass planning, operation, and expansion phases.